PENGARUH GREEN MARKETING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP BRAND IMAGE PADA PRODUK TUPPERWARE - Santoso, Voni Prila; Ardani, I Gusti Ayu Ketut Sri (E-Jurnal Manajemen, 2017)
This study aims to determine the effect of Green Marketing and Corporate Social Responsibility Brand Image on Tupperware products. The study population is consumer users Tupperware products. This study used a non-probability sampling techniques. Data were collected by distributing questionnaires, the number of respondents in this research were 100 respondents. The hypothesis was tested using the technique of path analysis (path analysis) and Sobel test. Hypothesis testing results showed that all the way down the hypothesis is accepted. Green marketing berpengaruf positively and significantly related to corporate social responsibility, green marketing and signikan positive effect on brand image, corporate social responsibility positive and significant impact on the brand image as well as green marketing positive and significant impact on the brand image through corporate social responsibility as mediation. Keywords: green marketing, corporate social responsibility, brand image